On the Relation Between Soft Electron Precipitations in the Cusp Region and Solar Wind Coupling Functions. Issue 1 (9th January 2018) - Dang, Tong; Zhang, Binzheng; Wiltberger, Michael; Wang, Wenbin; Varney, Roger; Dou, Xiankang; Wan, Weixing; Lei, Jiuhou
Abstract: In this study, the correlations between the fluxes of precipitating soft electrons in the cusp region and solar wind coupling functions are investigated utilizing the Lyon‐Fedder‐Mobarry global magnetosphere model simulations. We conduct two simulation runs during periods from 20 March 2008 to 16 April 2008 and from 15 to 24 December 2014, which are referred as "Equinox Case" and "Solstice Case, " respectively. The simulation results of Equinox Case show that the plasma number density in the high‐latitude cusp region scales well with the solar wind number density ( n cusp / n sw =0.78), which agrees well with the statistical results from the Polar spacecraft measurements. For the Solstice Case, the plasma number density of high‐latitude cusp in both hemispheres increases approximately linearly with upstream solar wind number density with prominent hemispheric asymmetry. Due to the dipole tilt effect, the average number density ratio n cusp / n sw in the Southern (summer) Hemisphere is nearly 3 times that in the Northern (winter) Hemisphere. In addition to the solar wind number density, 20 solar wind coupling functions are tested for the linear correlation with the fluxes of precipitating cusp soft electrons. The statistical results indicate that the solar wind dynamic pressure p exhibits the highest linear correlation with the cusp electron fluxes for both equinox and solstice conditions, with correlation coefficients greater than 0.75. The linear regression relations for equinox and solstice cases may provide an empirical calculation for the fluxes of cusp soft electron precipitation based on the upstream solar wind driving conditions. Key Points: Cusp plasma density correlates well with solar wind plasma density Cusp soft electron precipitations correlates best with SW dynamic pressure The direct‐entry cusp soft electron exhibits hemispheric asymmetry at solstice